How to create an investment portfolio of an individual investor - Pustaj, Marek; Zámečník, Petr; Smrčka, Luboš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
The goal of the thesis is to point out the necessity of the financial and investment planning, to describe and explain the basic rules and principles of the financial and investment planning and then create an investment portfolio of an individual investor. The thesis is divided into four main chapters, I start with a shorter chapter about inflation. Next chapter is dedicated to the entire process of financial planning. From the analysis, through a financial plan to the implementation and revision of the plan. Managing our finances we should follow mentioned rules and principles. The most relevant part of the financial plan is investment plan. So next chapter is dedicated to the investment planning. I make clear the basics of investment theory here. The last chapter is practical, it is the example of creating an investment portfolio of an individual investor.
Vedoucí práce: Petr Zámečník
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses